The Religious-Political Aspirations of North Korean Migrants and Protestant Churches in Seoul - Jung, Jin-Heon (2016)
This article highlights an aspiration specific to Seoul that is projected onto, experienced, and contested by North Korean refugee-migrants who have recently arrived by way of China in this capitalist city of a divided Korea. I pay particular attention to the role of the evangelical Protestant Church in the process of subjectification of these migrant individuals and the performative rituals by which they negotiate religious-political aspirations toward the future. The bodily-spiritual transformation of individual North Korean migrants into Christians is not strictly teleological and is more complicated, ambivalent, and diversified. By comparing two distinctive North Korean migrant activities—the balloon leaflet campaigns and the With-U music concerts and activities—this article discusses the efficacies of the performative rituals of violence and peace that contest and constitute the particular religious-political aspirations in the context of late-Cold War Seoul.
Keywords: Seoul; Conversion; evangelical Protestantism; North Korean migrants; religious-political aspirations